Language speaks. Heidegger’s Onto-historical Thought and the Enquiry into the Origins of Linguistic Significance - Leconte, Mariana (2015)
The present article discusses Heidegger's conception of language within the frame of his onto-historical thought. In order to address this issue he starts from the question about the origins oflinguistic significance which he identifies with the enquiry into the essence of language in relation with the act of “essencialization” of being. The analysis begins considering the metaphysical determination of the relationship between language and being in Aristotle to oppose its features to Heidegger’s distinctive one.